La tirannia della salute. Riflessioni giusfilosofiche sulla pandemia (Società e diritti, 2020)
Abstract: during the covid-19 pandemic, we all had to endure important limitations on our fundamental rights, which governments justified starting with the priority of the right to health. This absolutization of the right to health is not only not constitutionally founded, but is the subject of heated discussion in all scientific contexts, including the constitutional and bio-juridical ones. The article presents some considerations regarding this debate and proposes a conclusive reflection on the need to rethink individual rights – included right to health – in a solidarity and community framework.